Philosophy at the bedside – phenomenology, complexity and virtue in the care of patients. Issue 6 (29th September 2014) - Mitchell, Derek
Abstract Rationale, aims and objectives This personal reflection, based partly on my own experience as a patient, is written from the triple perspective of patient, former Health Service manager and philosopher. By beginning with the accounts of the first‐hand lived experiences of patients (my own and those of Havi Carel), which I argue are central to an understanding of illness, and by then moving through the complexity of the health care environment, I aim to show that only the promulgation of a virtue‐based theory of ethics and action can lead to real improvements in the quality of care delivered to patients. Methods The case is set out to bring together the philosophical insights of phenomenology, complexity theory and Virtue Ethics. Results The argument shows that only Virtue Ethics provides an adequate means to respond to the unique situation and feelings of the individual person who is ill. Conclusions This conclusion inevitably implies criticism of the ways that the performance of the institutions and the people who provide health care have been measured and regulated in the UK National Health Service. Overall the conclusions of this paper suggest that an approach based on virtuous agency and more closely directed towards the lived experience of people who are ill is needed to ensure both safety and improved quality in health care services.